TECHNIQUES OF NEWS WRITING IN IMPROVING THE QUALITY OF NEWS ON SOCIAL MEDIA YOUTUBE JURNAL 12 - Putri, Hanifah Priyani (QAULAN: Journal of Islamic Communication, 2022)
Abstract: The advantages of social media make it a popular medium to use. Jurnal 12 is a YouTube channel engaged in journalism. Carrying the topic of Indonesia's achievements, Jurnal 12 managed to get an audience of up to tens of thousands. The topic of Indonesia's achievements rarely gets attention. This study aims to explain the editorial techniques of Jurnal 12 in writing news and how the editorial staff of Jurnal 12 improves the quality of news. This study uses a qualitative method with a descriptive approach, using observation, documentation, and interview data collection procedures. The results from this study are:(1) in the October 1-31, 2021 edition, Jurnal 12 does not meet the rules of news writing. Jurnal 12 does not use leads; the use of the 'when' element is not optimal in formulating news. Jurnal 12 uses an inverted pyramid structure and always uses quotes. (2) to improve the quality of news, Jurnal 12 focuses on increasing the important elements: characters, conflicts, accuracy, and actuality.